Proceedings of the Thirteenth ACM International Conference on Information and Knowledge Management 2004
DOI: 10.1145/1031171.1031258
|View full text |Cite
|
Sign up to set email alerts
|

Event threading within news topics

Abstract: With the overwhelming volume of online news available today, there is an increasing need for automatic techniques to analyze and present news to the user in a meaningful and efficient manner. Previous research focused only on organizing news stories by their topics into a flat hierarchy. We believe viewing a news topic as a flat collection of stories is too restrictive and inefficient for a user to understand the topic quickly.In this work, we attempt to capture the rich structure of events and their dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
156
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 6 publications
1
156
0
2
Order By: Relevance
“…In the context of Topic Detection and Tracking (TDT) which is an area aims to effectively retrieve and organise broadcast news (speech) and newswire stories (text) into groups of events, Nallapati et al [16] have modelled the news topic based on event and their dependency. They named the process of recognizing events and identifying dependencies among them as event threading, an analogy to email threading that shows connections between related email messages.…”
Section: Event Crime Modelmentioning
confidence: 99%
“…In the context of Topic Detection and Tracking (TDT) which is an area aims to effectively retrieve and organise broadcast news (speech) and newswire stories (text) into groups of events, Nallapati et al [16] have modelled the news topic based on event and their dependency. They named the process of recognizing events and identifying dependencies among them as event threading, an analogy to email threading that shows connections between related email messages.…”
Section: Event Crime Modelmentioning
confidence: 99%
“…[2], [3], [4], [5], topic detection and tracking (TDT) [6], [7], [8], burstiness [9], [10], [11], [12], and various summarisation approaches using co-occurrence, such as [10], [13]. We aim at more flexible content sub-structures than the fixed "topics" of TTM and TDT and apply measures of burstiness and co-occurrence to characterise these.…”
Section: Related Workmentioning
confidence: 99%
“…8 Evaluations of search quality [1] demonstrated that the STORIES search finds coherent subsets of documents, that its quality is comparable to or better than state-of-the-art clustering, and that the tool enables people to answer questions on ground-truth events accurately and quickly.…”
Section: Evaluation Aspectsmentioning
confidence: 99%
“…For instance, Chen and Chen [4] summarized the incidents of a topic timeline to help readers understand the story of a topic quickly. Basically, a topic is associated with specific times, places, and persons [11]. Discovering the interactions between the persons can help readers construct the background of the topic and facilitate document comprehension.…”
Section: Introductionmentioning
confidence: 99%